2008
DOI: 10.1186/1757-1626-1-246
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction and pulmonary tuberculosis in a young female patient: a case report

Abstract: Introduction: Tuberculous coronaritis is known to be a very rare phenomenon, although Mycobacterium tuberculosis, as some other infectious agents, may also act in the coronary vessels by activating the inflammatory mechanism of atherosclerosis. The association between active pulmonary tuberculosis and acute myocardial infarction has not been reported for around three and a half decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Two main mechanisms have been suggested including increase in inflammation resulting in plaque formation and/or rapture and autoimmune phenomena [10].Our patient had some traditional risk factors for myocardial infarction including male gender, older age and hypertension and was diagnosed with active TB. There are several case reports of active TB and acute myocardial infarction including one case of a young female from Kosova with no known risk factors for ischemic heart disease suggesting TB as a potential pathogenic factor [11]. The presentation of TB with acute myocardial infarction (AMI) and aneurysm of the cardiac wall has as well been reported previously.…”
Section: Discussionmentioning
confidence: 75%
“…Two main mechanisms have been suggested including increase in inflammation resulting in plaque formation and/or rapture and autoimmune phenomena [10].Our patient had some traditional risk factors for myocardial infarction including male gender, older age and hypertension and was diagnosed with active TB. There are several case reports of active TB and acute myocardial infarction including one case of a young female from Kosova with no known risk factors for ischemic heart disease suggesting TB as a potential pathogenic factor [11]. The presentation of TB with acute myocardial infarction (AMI) and aneurysm of the cardiac wall has as well been reported previously.…”
Section: Discussionmentioning
confidence: 75%
“…Tuberculosis is also known to increase myocardial infarction rates, as demonstrated in a Taiwanese retrospective cohort, in which the TB group was 40% more likely to have had myocardial infarction [14] . Possible mechanisms of cardiovascular disease related to TB include indirect damage caused by systemic inflammation as well as direct injury of the heart [6] , [15] . Although rare, the latter has been shown in case reports of post-mortem histologic analyses of the heart [16] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent nationwide population-based cohort study has provided compelling evidence that tuberculosis patients are at higher risk of developing acute coronary syndrome (ACS), and that the risk increases with age (40). In addition, Bakalli et al (41) showed a rare case of AMI in a 30-year-old female patient with PTB. Kinare et al (42) reported a severe case of a 19-year-old male who died due to a large ventricular aneurysm obtained from myocardial infarction caused by tuberculous coronaritis of the LAD branch.…”
Section: Discussionmentioning
confidence: 99%